Technology : promises and problems : teacher's guide - Educational Research Council of America. Social Science Staff (Boston : Allyn and Bacon, 1977)
Explores the achievements and social problems and progress resulting from the scientific and technological revolutions.
Keywords: Technology -- Social aspects -- Juvenile literature; Technology -- Social aspects; Nature -- Effect of human beings on